Effect of a health literacy intervention trial on knowledge about cardiovascular disease medications among Indigenous peoples in Australia, Canada and New Zealand. Issue 1 (24th January 2018) - Crengle, Sue; Luke, Joanne N; Lambert, Michelle; Smylie, Janet K; Reid, Susan; Harré-Hindmarsh, Jennie; Kelaher, Margaret
Abstract : Objectives: To assess the effect of a customised, structured cardiovascular disease (CVD) medication health literacy programme on medication knowledge among Indigenous people with, or at high risk of, CVD. Design: Intervention trial with premeasures and postmeasures at multiple time points. Setting: Indigenous primary care services in Australia, Canada and New Zealand. Participants: 171 Indigenous people aged ≥20 years of age who had at least one clinical diagnosis of a CVD event, or in Canada and Australia had a 5-year CVD risk ≥15%, and were prescribed at least two of the following CVD medication classes: statin, aspirin, ACE inhibitors and beta blockers. Intervention: An education session delivered on three occasions over 1 month by registered nurses or health educators who had received training in health literacy and principles of adult education. An interactive tablet application was used during each session and an information booklet and pill card provided to participants. Primary outcome measures: Knowledge about the CVD medications assessed before and after each session. Results: Knowledge at baseline (presession 1) was low, with the mean per cent correct answers highest for statins (34.0% correct answers), 29.4% for aspirin, 26.0% for beta blockers and 22.7% for ACE inhibitors. Adjusted analyses showed highly significant (P<0.001) increases in knowledge scores between preassessments and postassessments at all three time points for all medication classes. For the four medications, the absolute increases in adjusted per cent correct items from presession 1 to postsession 3 assessments were 60.1% for statins, 76.8% for aspirin, 71.4% for ACE inhibitor and 69.5% for beta blocker. Conclusions: The intervention was highly effective in contextually diverse Indigenous primary healthcare services in Australia, Canada and New Zealand. The findings from this study have important implications for health services working with populations with low health literacy more generally. Trial registration number: ACTRN12612001309875.